Analysis of Participants Waiting Payment of JKN Mandiri Premium in the Working Area of the Helvetia Community Health Center - Asnila Dewi Harahap; Arifah Devi Fitriani; Deli Teo (Newinera Publisher, 2021)
The Mandiri National Health Insurance (JKN) is a national social security system where the premium is paid by participants. In 2018, data on premium arrears for Mandiri participants in Indonesia reached Rp. 5.7 Trillion, in Medan City, the highest premium arrears are in Medan Helvetia Subdistrict, amounting to IDR 4,215,379,613. The results of the initial survey indicate the cause of arrears is due to insufficient income. Green's theory explains that people's behavior in the health sector is formed due to a combination of predisposing, supporting and driving factors. This study aims to determine and analyze the influence of economic factors, knowledge, age, occupation and attitudes towards regulations in arrears of JKN Mandiri premium payments in the working area of Puskesmas Helvetia, Medan City. The research design used a quantitative analytic survey with a cross sectional approach. The study population was all JKN Mandiri participants in the work area of the Helvetia Health Center, Medan City who were in arrears, namely 8260 participants with a sample of 98 people. This research was conducted in the area of Helvetia Health Center, Medan City. Data were analyzed by univariate, bivariate and multivariate with multiple linear regression. The results showed that economic factors, knowledge and work have an influence in arrears of JKN Mandiri premium payments. Multivariate analysis shows that economic factors, knowledge, age, occupation and attitudes towards regulation only contribute to premium arrears of 19.7%. There is an influence of economic factors, knowledge and work in arrears to pay the JKN Mandiri premium, while the age factor, attitudes towards regulation have no effect. It is recommended for Puskesmas to always socialize JKN regulations and together with the local government to find solutions so that the community's economy will be better so that they can pay the JKN Mandiri premium.